2009
DOI: 10.1007/s11524-009-9409-9
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Residential Density with Adolescents’ Physical Activity in a Rapidly Urbanizing Area of Mainland China

Abstract: In the context of recent social and economic transitions in China, lack of physical activity among adolescents is an emerging health risk, particularly so in rapidly expanding urban areas. Evidence from Western countries suggests that built environment attributes can influence the physical activity participation of young people, but whether or not this is the case for China is unknown. We recruited high school students from ten urban districts in Nanjing, Mainland China (n=2,375; mean age=13.9± 1.0 years old; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 26 publications
2
53
1
1
Order By: Relevance
“…Respondents in these middle income neighborhoods with a lower State of Place™ Index did less walking for various purposes, which may at least partly explain their higher BMIs. Findings also challenged existing research (Xu et al, 2009(Xu et al, , 2010 that linked high density with low levels of (recreational only) physical activity.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Respondents in these middle income neighborhoods with a lower State of Place™ Index did less walking for various purposes, which may at least partly explain their higher BMIs. Findings also challenged existing research (Xu et al, 2009(Xu et al, , 2010 that linked high density with low levels of (recreational only) physical activity.…”
Section: Discussionmentioning
confidence: 54%
“…The few empirical studies conducted have produced some counterintuitive findings: in the Chinese context, high density has been associated with reduced recreational physical activity (Xu et al, 2009) and increased overweight (Xu et al, 2010). Extremely high density may limit open space and parks, leaving little space for walking or other physical activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the aspects of environments perceived to enhance walkability, and which are reviewed elsewhere in this paper, were not found to increase the amount of actual walking (also Bauman et al 2012). Logically, for example, places deemed "walkable" in one definition may be too convenient to allow much exercise (Van Dyck et al 2009a;Lovasi et al 2009;Gebel et al 2009Gebel et al , 2011Xu et al 2010).…”
Section: Exercise-inducingmentioning
confidence: 82%
“…Adults were the research subjects for three out of four studies. Only one study 32 focused on adolescents. Studies in the US and other developed countries showed that built environmental attributes might have different impacts on adults and children.…”
Section: Discussionmentioning
confidence: 99%